THE MULTIDIMENSIONAL NATURE OF KNOWLEDGE IN THE FIELD OF BIOLOGY AS A TOOL FOR THE REALIZATION OF EDUCATIONAL GOALS - Allanazarova I.A. (European Science Publishing, 2024)
It is known that "Biology" is the science of living organisms, and as in any natural science, its postulates are formed on the basis of proven scientific data, denying any unproven phenomenon. Simply put, modern biology is based only on facts, losing its axiological value due to the technological revolution. At the same time, if we turn to the origin of the development of biology as a science, it is clear that initially the surrounding world was perceived through the senses, and it is known from psychology that sensations are formed on the basis of information received from receptors. When a person perceives information through intuition, he forms his own vision of the world in his mind, and this is reflected in his behavior and actions in relation to the people around him and the external environment. If we turn biology into its sources of origin, it is possible to restore its moral, spiritual and educational role in the life of any person. The article describes ways to implement competence-based and educational goals in biology lessons in secondary and higher educational institutions.
Keywords: values, biology, morality, spirituality, competence, feelings, aesthetics.